Optimalisasi Pembelajaran Digital Menuju Era Digitalisasi Pendidikan Studi Kasus Di SMA Al Azhar 4 Kemang - Asrulla; Latif, Mukhtar; Anwar, Kasful; Jeka, Firdaus (Al-Riwayah : Jurnal Kependidikan, 2024)
This study aims to optimize learning in digital learning at SMA Islam Al Azhar 4 Kemang. Education significant transformation in the era of information technology, with the introduction of devices such as Smart Boards and iPads offering limitless potential in enhancing teaching and learning processes. This study uses a qualitative approach with a case study method. Data collection techniques used by the researcher are FGD (Focus Group Discussion) and observation. The data analysis technique used by the researcher is descriptive analysis. The results of the study show that the interest of students at SMA Islam Al Azhar 4 Kemang increased after the use of digital learning media in the form of Smart Boards and iPads. Students felt the effectiveness of using digital learning media. The findings of this study are that the use of iPads can provide significant benefits in digital learning at SMA Islam Al Azhar 4 Kemang if used appropriately. Various learning on iPads can increase student interaction and involvement in the learning process. In addition, the integration of rich multimedia features in Smart Boards and iPads helps to explain complex concepts more clearly and attractively. The challenges that need to be overcome so that the potential of Smart Boards and iPads can be truly maximized in learning at SMA Islam Al Azhar 4 Kemang are the difficulty in integrating this technology into the existing curriculum and finding a balance between the use of technology with traditional teaching methods.